Pelaksanaan Pembelajaran pada Anak Tuna Grahita di SDN Petir 3 Kota Tangerang - Nurfadhillah, Septy; Huwaida, Anbar Nisrina; Rizkyah, Khofifah; Fatharani, Julya (ALSYS, 2022)
This study aims to analyze the implementation of learning in mentally retarded children at SDN Petir 3 Tangerang City. This study uses a descriptive qualitative approach and the instruments used are observation, interviews, and documentation. The research subjects were homeroom teachers for grade 1, accompanying teachers for children with special needs (inclusion teachers), and school principals. The results show that SDN Petir 3 Tangerang City in implementing inclusive education has done well by ensuring that all learning runs properly and optimally.